Why does nitrogen addition to forest soils inhibit decomposition?. (October 2019) - Bonner, Mark TL.; Castro, David; Schneider, Andreas N.; Sundström, Görel; Hurry, Vaughan; Street, Nathaniel R.; Näsholm, Torgny
Abstract: Enrichment of forest soils with inorganic nitrogen (N) tends to inhibit oxidative enzyme expression by microbes and reduces plant litter and soil organic matter decomposition rates. Without further explanation than is currently presented in the scientific literature, we argue that upregulation of oxidative enzymes seems a more competitive response to prolonged N enrichment at high rates than the observed downregulation. Thus, as it stands, observed responses are inconsistent with predicted responses. In this article, we present a hypothesis that resolves this conflict. We suggest that high rates of N addition alter the competitive balance between enzymatic lignin mineralisation and non-enzymatic lignin oxidation. Using metatransciptomics and chemical assays to examine boreal forest soils, we found that N addition suppressed peroxidase activity, but not iron reduction activity (involved in non-enzymatic lignin oxidation). Our hypothesis seems positioned as a parsimonious and empirically consistent working model that warrants further testing. Highlights: Our hypothesis predicts increased nonenzymatic oxidation relative to enzymatic with N. RNA data indicated a big drop in white rot but not brown rot oxidation with N. Chemical assays showed strong reduction in peroxidases but not iron reduction with N. Together, this suggests a higher ratio of nonenzymatic to enzymatic oxidation with N.